Biological Variables Contributing to Heat Stress in Dairy Cattle: Comprehensive Analysis - Kumud Saxena, A Rengarajan, Rakesh Kumar Yadav (Revista Electronica de Veterinaria, 2024)
Heat stress (HS) is an imminent threat to the production well-being and sustainability of dairy farms. Recognizing the complex biological factors driving HS in dairy cattle is crucial for developing effective mitigation techniques as global temperature increases.The well-being of animals can be significantly impacted when dairy cattle are subjected to HSdue to the conditions. As the population of high milk-yielding production animals with increased metabolic activity continues to grow, the challenges in managing HS have reached unprecedented levels.The aim of this research was to examine the variations in the biological characteristics of dairy cows and determine which biological markers exhibit more reliability when it comes to verifying HS.Moreover, the research gathered the biological variables, which included heart rate (HR), respiration rate (RR), rectal temperature (RT), andserum hormones concentrations from 110 dairy cows and analyzed them for 30 Days.It is crucial to have a grasp of the biological variables that cause HS in dairy cattle to create management strategies that protect the animals, increase their productivity, and guarantee that dairy farming can continue even when the environment changes.Statistical analysis was used to analyze the data, the MIXED technique was used for mixed form equations to infer fixed and random effects. Exploring HS in dairy cattle’s complex biological variables improves our understanding of physiological responses to elevated temperatures and enables the development of targeted interventions and precision management strategies to improve dairy herd resilience and well-being under changing climates.Since respiratory rate is the most adapted biological metric to HS, it is the greatest predictor of HS in dairy cattle.